Characteristics of Professional Burnout of Administrative and Managerial Personnel of Russian Educational Organizations in the Context of the Introduction of Innovative Technologies - Sofia S. Belousova (Peoples' Friendship University of Russia (RUDN University), 2021)
The specifics of professional burnout of teachers engaged, in addition to their direct pedagogical activities, in the administration of their educational organizations are studied. The relevance of the raised research problem is determined by the significant socio-economic and political changes taking place in the modern education system: its intensive modernization and the introduction of innovative technologies in education have an impact not only on the content side of the educational process but also on its organization. The implementation of these innovations falls on the shoulders of the administrative and managerial personnel of schools, demanding huge emotional, intellectual and mental costs from the latter. The purpose of this study was to identify the characteristics of professional burnout and its symptoms in administrative and managerial personnel of educational organizations in relation to the severity of their psychological defenses and personality motivational profile. The sample was composed of 75 teachers (54 women, 21 men) in the position of school deputy director for studies and educational work. Their administrative work experience in an educational organization ranged from 1 to 23 years, the average age was 37.5 years. The study used a set of valid and reliable psychodiagnostic methods, including The Maslach Burnout Inventory (MBI) Questionnaire by Ch. Maslach and S.E. Jackson (adapted by N.E. Vodopyanova), The Life Style Index (LSI) by R. Plutchik, H. Kellerman and H.R. Conte (adapted by E.S. Romanov and L.R. Grebenshchikov) and Diagnosis of the Motivational Structure of Personality by V. Milman. The correlation analysis revealed that among teachers who additionally occupy in an educational institution, professional burnout is interconnected with the manifestation of psychological defenses of suppression, projection and intellectualization. Also, a relationship was established between professional burnout and a decrease in motivation for communication, general activity, creative activity and social usefulness of activities. The revealed specifics of professional activity and burnout of school deputy directors as well as the characteristics of their strategies for overcoming crisis situations in professional activity under conditions of changes and uncertainties open up opportunities for us to develop and implement programs on preventing professional burnout in this category of teachers and providing psychological support for their professional activities.